Implementasi Sistem Informasi Penjualan Berbasis Web Menggunakan Framework Laravel 12 : Studi Kasus Pada Toko Ulkids Pegandon - Shofa Arinal Hakikiyah; Bagus Sudirman; Ahmad Ashifuddin Aqham; Dendy Kurniawan; Moh. Muthohir (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This study, titled “Implementation of a Web-Based Sales Information System Using the Laravel 12 Framework: A Case Study at Ulkids Store Pegandon,” was conducted to address declining sales performance caused by conventional sales processes and manual transaction management. Ulkids Store experienced a 62.6% decrease in profit from 2019 to 2025, mainly due to limited promotional reach, inaccurate stock recording, and inefficient sales transactions. The research aims to design and implement a web-based sales information system to improve transaction efficiency, data accuracy, and customer accessibility. A qualitative approach with a case study method was applied, while system development followed the Waterfall model. The system was built using Laravel 12, PHP, MySQL, and a Bootstrap 5 user interface, and was tested using Black Box Testing to ensure all functions operated according to user requirements.